An ocular Th1 immune response promotes corneal nerve damage independently of the development of corneal epitheliopathy - Vereertbrugghen, Alexia (2023)
Proper sight is not possible without a smooth, transparent cornea, which is highly exposed to environmental threats. The abundant corneal nerves are interspersed with epithelial cells in the anterior corneal surface and are instrumental to corneal integrity and immunoregulation. Conversely, corneal neuropathy is commonly observed in some immune-mediated corneal disorders but not in others, and its pathogenesis is poorly understood. Here we hypothesized that the type of adaptive immune response may influence the development of corneal neuropathy. To test this, we first immunized OT-II mice with different adjuvants that favor T helper (Th)1 or Th2 responses. Both Th1-skewed mice (measured by interferon-γ production) and Th2-skewed (measured by interleukin-4 production) developed comparable ocular surface inflammation and conjunctival CD4+ T cell recruitment but no appreciable corneal epithelial changes upon repeated local antigenic challenge. Th1-skewed mice showed decreased corneal mechanical sensitivity and altered corneal nerve morphology (signs of corneal neuropathy) upon antigenic challenge. However, Th2-skewed mice also developed milder corneal neuropathy immediately after immunization and independently of ocular challenge, suggestive of adjuvant-induced neurotoxicity. All these findings were confirmed in wild-type mice. To circumvent unwanted neurotoxicity, CD4+ T cells from immunized mice were adoptively transferred to T cell-deficient mice. In this setup, only Th1-transferred mice developed corneal neuropathy upon antigenic challenge. To further delineate the contribution of each profile, CD4+ T cells were polarized in vitro to either Th1, Th2, or Th17 cells and transferred to T cell-deficient mice. Upon local antigenic challenge, all groups had commensurate conjunctival CD4+ T cell recruitment and macroscopic ocular inflammation. However, none of the groups developed corneal epithelial changes and only Th1-transferred mice showed signs of corneal neuropathy. Altogether, the data show that corneal nerves, as opposed to corneal epithelial cells, are sensitive to immune-driven damage mediated by Th1 CD4+ T cells in the absence of other pathogenic factors. These findings have potential therapeutic implications for ocular surface disorders.